Students' Mathematical Communication Skills In Solving Mathematical Problems Based On Learning Styles - Noviana Dini Rahmawati; Stevanus Budi Waluya; Nuriana Rachmani Dewi (Universitas Negeri Semarang, 2022)
Students' mathematical communication skills are still not optimal, this can be seen when students have difficulty in expressing their mathematical ideas in the form of writing or pictures. Students can understand the meaning of the problem given, but have difficulty communicating it again in the form of a mathematical model. This study aims to determine the mathematical communication skills of class VIII students in solving mathematical problems based on visual and auditory learning styles. The subjects of this study were eighth grade students of SMP Negeri 25 Semarang, each with one student with a visual learning style and one student with an auditory learning style. Data collection techniques used questionnaires to classify students based on learning styles, written tests, and interviews to determine students' mathematical communication skills. The validity test of the data used is triangulation technique by comparing the results of the written test and the results of the interview. The results of the study concluded that both students with a visual learning style and students with an auditory learning style have met the indicators of expressing everyday events into language or mathematical symbols and can explain ideas, situations, and mathematical relationships with real objects, pictures, graphs, and algebra . However, students with an auditory learning style have a higher level of accuracy than students with a visual learning style in writing mathematical symbols in the process of solving problems in solid-sided geometric material.